The Impact of Same- and Other-Race Gaze Distractors on the Control of Saccadic Eye Movements. (August 2015) - Dalmaso, Mario; Galfano, Giovanni; Castelli, Luigi
Two experiments were aimed at investigating whether the implementation of voluntary saccades in White participants could be modulated more strongly by gaze distractors embedded in White versus Black faces. Participants were instructed to make a rightward or leftward saccade, depending on a central directional cue. Saccade direction could be either congruent or incongruent with gaze direction of the distractor face. In Experiment 1, White faces produced greater interference on saccadic accuracy than Black faces when the averted-gaze face and cue onset were simultaneous rather than separated by a 900-ms asynchrony. In Experiment 2, two temporal intervals (50 ms vs . 1, 000 ms) occurred between the initial presentation of the face with direct-gaze and the averted-gaze face onset, whereas the averted-gaze face and cue onset were synchronous. A greater interference emerged for White versus Black faces irrespective of the temporal interval. Overall, these findings suggest that saccadic generation system is sensitive to features of face stimuli conveying eye gaze.